2008
DOI: 10.1590/s1516-31802008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal metaplasia in gallbladders: prevalence study

Abstract: CONTEXT AND OBJECTIVE: Gallbladder cancer is usually diagnosed at a late stage and generally results in death. Discovery of predisposing factors for this neoplasia could prevent this outcome. In this study, we assess the presence of one of these factors: intestinal metaplasia in gallbladders with stones and inflammatory processes. DESIGN AND SETTING: Cross-sectional study in Hospital do Servidor Público Estadual de São Paulo. METHOD: The first 80 gallbladders from patients who underwent elective cholecystectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
3
8
0
2
Order By: Relevance
“…In this same age group, they observed a greater number of cases of intestinal and pyloric metaplasia. Duarte and associates and Fernandes and associates also observed a bigger incidence of pyloric and intestinal metaplasia within patients over 50 years of age 19,32…”
Section: Discussionmentioning
confidence: 91%
“…In this same age group, they observed a greater number of cases of intestinal and pyloric metaplasia. Duarte and associates and Fernandes and associates also observed a bigger incidence of pyloric and intestinal metaplasia within patients over 50 years of age 19,32…”
Section: Discussionmentioning
confidence: 91%
“…Metaplasia is believed to be a strong histological sign for diagnosis of moderate or severe chronic cholecystitis because it is rarely observed in gallbladder autospy in which only mild inflammatory changes present. [36] Misra et al [37] found that H. pylori colonises areas of metaplasia in gallbladder producing histological changes very similar to those seen in gastric mucosa. Chen et al [38] demonstrated that metaplasia may provide suitable conditions for H. pylori colonization in the gallbladder.…”
Section: Discussionmentioning
confidence: 95%
“…Cellular differentiation begins in the GB due to inflammation and other factors added to the GB, resulting in intestinal metaplasia (IM). Increased cell damage causes dysplasia and ultimately carcinoma in situ [10, 11]. Development of dysplasia-carcinoma in the GB is a long process.…”
Section: Introductionmentioning
confidence: 99%